A rare case report of Urinary Bladder Paraganglioma - Rai, Ujwal; Shah, Amit Kumar; Sharma, Umesh Kumar (Medical Journal of Eastern Nepal, 2022)
Paragangliomas are extra-adrenal tumors of the autonomic nervous system which is termed pheochromoctyoma in adrenal gland. These tumors are found within the skull base, neck, mediastinum and periaortic region. Paragangliomas of the urinary bladder are rare, and non-functioning bladder paraganglioma is even rarer and not easily recognized. Histopathological examination of the tumor is essential to establish the diagnosis of paraganglioma. This is a case report of 67year male patient presenting with hematuria and passage of blood clots per urethra in emergency department. Cystoscopic examination revealed an exophytic growth in upper posterior wall of his bladder with areas of hemorrhagic blood clots within the vicinity of growth. His blood pressure was found 120/75 mm of Hg with normal serum sodium and potassium levels. Bipolar transurethral resection of the bladder mass was performed. Intraoperative procedure was uneventful and no rise in blood pressure during resection was found. Histopathological examination with immunohistochemistry confirmed diagnosis paraganglioma, urinary bladder. Patient is doing well and is kept on follow up.